Integration of Islam And Local Culture In The Art of Shalawat Ngelik In The Village of Mlangi Yogyakarta - Sasadara; Badrun Badrun (Institut Agama Islam Negeri Jember, 2022)
Religion and culture both influence each other and cannot be separated. When religion entered the cultural sphere, religion became the heart of culture. Islam began to try to incorporate elements of the values ??of its teachings into Javanese culture without losing its original elements to create the integration of religion and local culture. One manifestation of the integration of Islam and local culture is in the arts. Art is one of the elements of culture which is the result of the creation of human creativity as an expression of feelings of the heart. Shalawat Ngelik is art with Islamic breath that has been acculturated with Javanese culture in Mlangi Hamlet. Shalawat Ngelik is the recitation of the Prophet's Shalawat by using the rhythm of the Javanese style with a shrill voice or high intonation. This study uses the historical method as the method of analysis. The author is interested in studying and analyzing the integration between Islam and Javanese culture in the art of Shalawat Ngelik. Through this research, the writer knows that Shalawat Ngelik is a new culture resulting from a cross between Islamic and Javanese culture; besides that Shalawat Ngelik also has a deep meaning for the life of the Mlangi Community.